2023
DOI: 10.3390/inorganics11080324
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative, Genotoxic and Cytotoxic Damage Potential of Novel Borenium and Borinium Compounds

Sibel Bayil Oguzkan,
Hasan Turkez,
Halil Ibrahim Ugras
et al.

Abstract: In this study, the biological properties of novel borenium and borinium compounds in terms of their oxidative, genotoxic, and cytotoxic effects were assessed on cultured human peripheral blood cells, as well as several types of cancer cells. Our results revealed that the borinium compounds yielded the best results in terms of supporting total antioxidant capacity (TAC). In fact, borenium 1, borenium 2, borenium 3, borinium 4, and borinium 5 compounds elevated TAC levels of cultured human blood cells at rates o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 68 publications
0
1
0
Order By: Relevance
“…In this regard, Ortiz-Flores et al carried out the identification of BCCs active on triple-negative breast cancer cells; they demonstrated that phenanthren-9-yl boronic acid and 6-hydroxynaphthalen-2-yl boronic acid have cytotoxic properties at sub-micromolar concentrations; however, the establishment of the mechanism of action requires additional evaluation [10]. Meanwhile, Oguzcan et al reported borenium and borinium derivatives as safe compounds in healthy human cells, but with moderate action against glioblastoma, neuroblastoma, prostate, and pharyngeal cancer cell lines [11].…”
mentioning
confidence: 99%
“…In this regard, Ortiz-Flores et al carried out the identification of BCCs active on triple-negative breast cancer cells; they demonstrated that phenanthren-9-yl boronic acid and 6-hydroxynaphthalen-2-yl boronic acid have cytotoxic properties at sub-micromolar concentrations; however, the establishment of the mechanism of action requires additional evaluation [10]. Meanwhile, Oguzcan et al reported borenium and borinium derivatives as safe compounds in healthy human cells, but with moderate action against glioblastoma, neuroblastoma, prostate, and pharyngeal cancer cell lines [11].…”
mentioning
confidence: 99%